Thomas Blunt papers - Blunt, Thomas, active 1815-1841.
Account book (1835-1841) and 16 account fragments (1815-1841), kept by Blunt in Powhatan County, Va.
Accountant.
Collection material in English.
Keywords: Business records -- Virginia -- Powhatan County; Accountants